Polyethylene preservative film as well as preparation method and application thereof in field of rubber tires
By using polyethylene composition, auxiliary resin and modified zinc oxide filler in polyethylene plastic wrap to form a composite structure and a multi-layer film structure, the existing polyethylene isolation film is solved, and the mechanical and durability of the film is significantly improved, and it is suitable for high-temperature or high-humidity environments.
Patent Information
- Application Number
- CN202510015515.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
AI Technical Summary
The existing polyethylene isolation film is prone to tensile deformation, wrinkle or damage during tire manufacturing, and cannot maintain the stability of physical properties under high temperature or high humidity environments, affecting production efficiency and rubber sheet quality.
The combination of polyethylene composition, auxiliary resin, modified zinc oxide filler and specific dispersant is adopted to form a composite structure and a multi-layer film structure by modifying zinc oxide to enhance the mechanical properties of the film, waterproof, heat resistance and aging resistance.
It significantly improves the mechanical properties, waterproof, heat resistance, aging resistance and corrosion resistance of polyethylene plastic wrap, meets the high-performance needs of modern tire manufacturing industry, and is suitable for high-temperature or high-humidity environments.
Smart Images

Figure BDA0005229798790000141
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer film materials, and in particular to a polyethylene cling film and a preparation method thereof, and applications in the field of rubber tires. Background Art
[0002] In the manufacturing process of rubber tires, especially in the production of all-steel radial tires and semi-steel radial tires, isolation films are widely used in multiple production links as an important auxiliary material. The main functions of isolation films include: preventing the uncured rubber sheet from direct contact with the air, avoiding oxidation of the rubber sheet surface, maintaining the original viscosity of the rubber, and preventing adhesion between rubber sheets to ensure smooth subsequent processing. In addition, isolation films also have the functions of preservation, dust prevention, and light shielding, which play a vital role in ensuring the quality of tires and extending the service life of tires.
[0003] Traditional separators are mostly made of polyethylene (PE), which is widely used due to its good flexibility and processing performance. However, with the development of tire manufacturing technology and the improvement of environmental awareness, the requirements for separators are also increasing. Not only do they need to meet basic functional requirements, but they also need to have better physical and mechanical properties, such as higher tensile strength, better resilience and longer service life, to adapt to modern efficient and energy-saving tire production lines.
[0004] Although the existing polyethylene isolation cling film can meet the basic needs of tire manufacturing to a certain extent, there are still some significant problems: for example, the traditional disposable polyethylene isolation film is prone to stretching, wrinkling and even breakage, which not only affects the production efficiency but also may damage the quality of the rubber sheet; in certain special working environments, such as high temperature or high humidity conditions, the existing isolation film may not be able to maintain the stability of its physical properties, thereby affecting the use effect of the isolation film.
[0005] Therefore, in order to solve the above problems, the present application provides a polyethylene cling film and a preparation method thereof. The polyethylene cling film prepared in the present application not only has excellent mechanical properties, but also can ensure good waterproof, heat-resistant, aging-resistant and corrosion-resistant properties, effectively meeting the performance requirements of the existing tire manufacturing industry for polyethylene cling film, and has very excellent application prospects. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present application provides a polyethylene cling film, the raw materials of which are, by mass: 80 to 120 parts of polyethylene composition, 20 to 40 parts of auxiliary resin, 10 to 20 parts of filler, 1 to 2 parts of antioxidant, 1 to 1.5 parts of antistatic agent, 0.4 to 0.8 parts of light stabilizer, 0.5 to 1.5 parts of lubricant, 5 to 12 parts of dispersant, 3 to 6 parts of plasticizer, and 0.5 to 1 part of cross-linking agent.
[0007] As a preferred solution, the polyethylene composition is a linear low-density polyethylene, or a composition of low-density polyethylene and high-density polyethylene.
[0008] As a preferred solution, the mass ratio of the linear low-density polyethylene, low-density polyethylene and high-density polyethylene is (40-60): (20-30): (10-20).
[0009] As a preferred solution, the mass ratio of the polyethylene composition, the auxiliary resin and the filler is (95-110): (25-35): (12-18).
[0010] As a preferred solution, the mass ratio of the polyethylene composition, the auxiliary resin and the filler is (100-105): (28-32): (14-16).
[0011] As a preferred solution, the mass ratio of the filler to the dispersant is (12-18): (6-8).
[0012] As a preferred solution, the auxiliary resin is a composition of maleic anhydride grafted polyethylene and ethylene-vinyl acetate copolymer.
[0013] As a preferred solution, the mass ratio of the maleic anhydride grafted polyethylene to the ethylene-vinyl acetate copolymer is (5-6):(1.5-2).
[0014] As a preferred solution, the filler is a composition of talc, diatomaceous earth and modified zinc oxide.
[0015] As a preferred solution, the mass ratio of talc powder, diatomaceous earth and modified zinc oxide is (4-5): (1-2): (7-9).
[0016] As a preferred solution, the mass ratio of talcum powder, diatomaceous earth and modified zinc oxide is 4.5:2:8.5.
[0017] As a preferred solution, the average particle size of the talc powder is 1 to 1.5 μm.
[0018] As a preferred scheme, the preparation method of the modified zinc oxide includes the following steps: S1: zinc oxide and zirconium chloride hexahydrate are mixed and added to a DMF solution, glutaric anhydride and 3-aminopropyltriethoxysilane are added, the temperature is raised to 70-75°C and kept warm for 2-3 hours, and after completion, the product is centrifuged and filtered, washed and dried to obtain pre-treated mixed particles; S2: 1,4-phthalic acid and 1,4-aminophthalic acid are added to DMF and stirred to form an acid mixed solution for standby use, the pre-treated mixed particles are dispersed in the DMF solution and then added dropwise to the acid mixed solution, the dropping time is 1-1.5 hours, and the dropping reaction temperature is 80-90°C; S3: after the dropwise addition is completed, the reaction container is sealed, the temperature is raised to 120-140°C, and the temperature is kept for reaction for 16-18 hours. After completion, the product is naturally cooled to room temperature, and DMF and anhydrous ethanol are washed alternately for 2-3 times. Finally, the cleaned product is placed in a vacuum drying oven and dried overnight at 80-90°C.
[0019] As a preferred solution, the mass ratio of zinc oxide, zirconium chloride hexahydrate, glutaric anhydride and 3-aminopropyltriethoxysilane is (0.5-0.8): (1.5-2): (0.3-0.4): (0.05-0.1).
[0020] As a preferred solution, in the pretreated mixed particles, the mass ratio of 1,4-phthalic acid to 1,4-aminophthalic acid is (2-2.5): (1.2-1.5): (0.3-0.5).
[0021] As a preferred solution, the average particle size of the zinc oxide is 15 to 20 nm; the average particle size of the modified zinc oxide is 620 to 720 nm.
[0022] In this application, by adding the above-mentioned modified zinc oxide filler, and its compound combination with a specific dispersant, the mechanical, waterproof, moisture-resistant, heat-resistant, aging-resistant and corrosion-resistant properties of polyethylene cling film can be greatly increased. The added modified zinc oxide can actually form a composite structure with zinc oxide microparticles as the surface embedded coating and the framework particles as the center. The existence of this structure can make full use of the hydrogen bonding effect between the surface hydroxyl group and the resin group, greatly increase the connection effect of the particles inside the resin system, and then use the particles as uniformly dispersed connection mechanical sites. The existence of this site can become a connection "button" when an external force acts to greatly enhance the mechanical properties of polyethylene cling film; and by controlling the particle size and overall particle size of the surface particles, the exposed area of the framework particles in the surface can also be controlled, thereby avoiding the hydrophilic effect caused by the introduction of a large number of surface hydroxyl groups, and the specific dispersant added in this application can form a multilayer film structure, increase the surface smoothness of the cling film, and thereby avoid the formation of a surface hydration layer due to the "water storage" characteristics of the rough peak-valley structure on the surface of the film, thereby greatly improving the waterproof, moisture-resistant, corrosion-resistant and heat-resistant aging properties of the cling film.
[0023] As a preferred solution, the antioxidant is at least one of 2,6-di-tert-butylated p-cresol, butylated hydroxyanisole, tert-butylhydroquinone, antioxidant 1010, antioxidant 1076, antioxidant 168 and antioxidant 622.
[0024] As a preferred solution, the antioxidant is 2,6-di-tert-butyl-p-cresol.
[0025] As a preferred solution, the light stabilizer is at least one of UV-531, UV-328, UV-9, UV-320, CHINOX 770 and Tinuvin 770.
[0026] As a preferred solution, the light stabilizer is UV-531.
[0027] As a preferred solution, the lubricant is a composition of zinc stearate and glyceryl stearate.
[0028] As a preferred solution, the mass ratio of zinc stearate to glyceryl stearate is (5-7):(2-2.5).
[0029] As a preferred solution, the plasticizer is at least one of dibutyl phthalate, dioctyl phthalate, acetyl tributyl citrate, triethyl citrate, epoxy octyl decanoate and triphenyl phosphate.
[0030] As a preferred solution, the plasticizer is a combination of dibutyl phthalate and triphenyl phosphate.
[0031] As a preferred solution, the mass ratio of dibutyl phthalate to triphenyl phosphate is (8-10):(2-3).
[0032] As a preferred solution, the crosslinking agent is at least one of dicumyl peroxide, di-tert-butyl peroxide, dibenzoyl peroxide, azobisisobutyronitrile and vinyltriethoxysilane.
[0033] As a preferred solution, the cross-linking agent is dicumyl peroxide.
[0034] As a preferred solution, the dispersant is a composition of phenethylphenol polyoxyethylene ether and epoxy front-stage polymer.
[0035] As a preferred solution, the mass ratio of the phenethylphenol polyoxyethylene ether to the epoxy front-stage polymer is (3-3.5): (1.5-2).
[0036] As a preferred solution, the HLB value of the phenethylphenol polyoxyethylene ether is 10-14.
[0037] As a preferred solution, the weight average molecular weight of the epoxy front-stage polymer is 1500-5000Da.
[0038] As a preferred solution, the epoxy front-stage polymer is a composition of an ethylene oxide-propylene oxide block copolymer with a weight average molecular weight of 1500-2000Da and an ethylene oxide-propylene oxide block copolymer with a weight average molecular weight of 4000-5000Da, and the mass ratio of the two is (4-5): (1.5-2.5).
[0039] The second aspect of the present application provides a preparation method of the above-mentioned polyethylene cling film, which specifically comprises the following steps: S1: mixing a polyethylene composition, an auxiliary resin, a filler and a dispersant, and adding the mixture to a high-speed mixer, mixing them uniformly at a rotation speed of 600 to 800 rpm for 30 to 35 minutes, and then adding the remaining raw materials, increasing the rotation speed to 1200 to 1500 rpm, and mixing for 10 to 15 minutes; S2: adding the mixed raw materials to a twin-screw extruder, setting the temperature of the extruder to 180 to 220° C. and the screw speed to 200 to 300 rpm, and performing melt extrusion, and the extruded melt is extruded into a film through a die head; S3: the extruded film melt is rapidly cooled and shaped by a water-cooled roller, the temperature of the water-cooled roller is controlled at 20 to 30° C., and the cooling speed is 2 to 4 m / min; S4: the film after cooling and shaping is towed by a towing device at a towing speed of 5 to 7 m / min, and then rolled up, and the film is obtained after completion.
[0040] The third aspect of the present application provides an application of the above-mentioned polyethylene cling film in the field of rubber tires.
[0041] The polyethylene cling film prepared in the present application is an isolation cling film specially used in the production process of all-steel and semi-steel radial tires. It is mainly used in the calendering, two-composite truncation, belt layer and other processes in tire production, which can effectively solve the problem of maintaining the freshness of rubber for a long time in the tire production process, and further improve its use quality (mechanical properties) and life (aging resistance), and can maintain excellent performance in certain special working environments, such as high temperature or high humidity conditions (high temperature resistance, waterproof and moisture resistance).
[0042] The beneficial effects of this application are:
[0043] 1. The polyethylene cling film provided in the present application not only has excellent mechanical properties, but also can ensure good waterproof, heat-resistant, aging-resistant and corrosion-resistant properties, effectively meeting the performance requirements of the existing tire manufacturing industry for polyethylene cling film, and has very excellent application prospects.
[0044] 2. A polyethylene cling film provided in the present application, the added modified zinc oxide can actually form a composite structure with zinc oxide microparticles as the surface embedded coating and the framework particles as the center. The existence of this structure can fully utilize the hydrogen bonding effect between the surface hydroxyl groups and the resin groups, greatly increase the connection effect of the particles inside the resin system, and then use the particles as uniformly dispersed connection mechanical sites. The existence of this site can become a connecting "button" when an external force acts, greatly enhancing the mechanical properties of the polyethylene cling film.
[0045] 3. A polyethylene cling film provided in the present application, in which the added modified zinc oxide can control the exposed area of the framework particles on the surface by controlling the particle size and the overall particle size of the surface particles, thereby avoiding the hydrophilic effect caused by the introduction of a large number of surface hydroxyl groups, and can form a multilayer film structure in combination with the specific dispersant added in the present application, thereby increasing the surface smoothness of the cling film, thereby avoiding the formation of a surface hydration layer due to the "water storage" characteristics of the rough peak-valley structure on the film surface, thereby greatly improving the waterproof, moisture-resistant, corrosion-resistant and heat-resistant aging properties of the cling film. DETAILED DESCRIPTION
[0046] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0047] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0048] Example 1
[0049] Example 1 The first aspect provides a polyethylene cling film, the raw materials of which are, by mass: 105 parts of a polyethylene composition, 30.5 parts of an auxiliary resin, 15 parts of a filler, 1.1 parts of an antioxidant, 1.2 parts of an antistatic agent, 0.6 parts of a light stabilizer, 1.2 parts of a lubricant, 7.2 parts of a dispersant, 5.5 parts of a plasticizer, and 0.8 parts of a cross-linking agent.
[0050] The polyethylene composition is a composition of linear low-density polyethylene, low-density polyethylene and high-density polyethylene, and the mass ratio of the three is 55:30:20.
[0051] Linear low-density polyethylene was purchased from Jiangsu Weirun High-Plastic Chemical Co., Ltd. under the model DFDA-7042.
[0052] Low-density polyethylene was purchased from Shanghai Hengfeng Plastic Chemical Co., Ltd. as model 2426H.
[0053] The high-density polyethylene was purchased from DGDA-6097 product sold by Sinopec.
[0054] The auxiliary resin is a composite of maleic anhydride grafted polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of the two is 5.5:2.
[0055] The maleic anhydride grafted polyethylene was purchased from the OE825 model product sold by Shanghai Wanluji Plastic Technology Co., Ltd.; the ethylene-vinyl acetate copolymer was purchased from the EVA18J3 model product sold by Suzhou Yitianli Plastic Co., Ltd.
[0056] The filler is a composition of talcum powder, diatomaceous earth and modified zinc oxide, and the mass ratio of the three is 4.5:2:8.5.
[0057] The average particle size of talc is 1.2 μm.
[0058] The preparation method of modified zinc oxide comprises the following steps: S1: 0.6 parts of zinc oxide and 1.8 parts of zirconium chloride hexahydrate are mixed and added to 60 parts of DMF solution, 0.32 parts of glutaric anhydride and 0.08 parts of 3-aminopropyltriethoxysilane are added, the temperature is raised to 70°C and kept warm for 2.5 hours, after completion, the product is centrifuged and filtered, washed and dried to obtain pretreated mixed particles; S2: 1.5 parts of 1,4-phthalic acid and 0.4 parts of 1,4-aminophthalic acid are added to 100 parts of DMF and stirred. Stir thoroughly to form an acid mixed solution for use, disperse 2.2 parts of pretreated mixed particles in 40 parts of DMF solution and then add dropwise to the acid mixed solution, the dropping time is 1 hour, and the dropping reaction temperature is 85°C; S3: after the dropping is completed, seal the reaction container, heat it to 130°C, and keep the reaction for 18 hours. After completion, naturally cool the product to room temperature, wash it alternately with DMF and anhydrous ethanol 3 times, and finally place the cleaned product in a vacuum drying oven, dry it at 85°C overnight, and it is completed.
[0059] The average particle size of zinc oxide is 18 nm; the average particle size of modified zinc oxide is 677 nm.
[0060] The antioxidant is 2,6-di-tert-butyl-p-cresol; the light stabilizer is UV-531.
[0061] The lubricant is a composition of zinc stearate and glyceryl stearate, and the mass ratio of the two is 5.5:2.4.
[0062] The plasticizer is a composition of dibutyl phthalate and triphenyl phosphate, and the mass ratio of the two is 9:2.4.
[0063] The crosslinking agent is dicumyl peroxide.
[0064] The dispersant is a composition of phenethylphenol polyoxyethylene ether and epoxy pre-stage polymer, and the mass ratio of the two is 3.4:1.6.
[0065] The HLB value of phenylethylphenol polyoxyethylene ether is 12.5, and the corresponding HLB product was purchased from Haian Petrochemical Company in Jiangsu Province.
[0066] The epoxy front-stage polymer is a composition of an ethylene oxide-propylene oxide block copolymer with a weight average molecular weight of 1700Da (BASF, L42 model) and an ethylene oxide-propylene oxide block copolymer with a weight average molecular weight of 4200Da (BASF, L84 model), and the mass ratio of the two is 4.5:2.
[0067] The second aspect of the present embodiment provides a preparation method of the above-mentioned polyethylene cling film, which specifically includes the following steps: S1: After mixing the polyethylene composition, auxiliary resin, filler and dispersant, add them to a high-speed mixer, mix them evenly at a rotation speed of 750rpm, and the mixing time is 30min. After completion, add the remaining raw materials, increase the rotation speed to 1400rpm, and mix for 12min; S2: Add the mixed raw materials to a twin-screw extruder, set the temperature of the extruder to 210°C and the screw speed to 240rpm, and perform melt extrusion. The extruded melt is extruded into a film through a die head; S3: The extruded film melt is quickly cooled and shaped by a water-cooled roller, the temperature of the water-cooled roller is controlled at 25°C, and the cooling rate is 3m / min; S4: The cooled and shaped film is towed by a towing device at a towing speed of 6m / min, and then rolled up. After completion, it is obtained.
[0068] Example 2
[0069] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the polyethylene cling film, in parts by mass, are: 95 parts of a polyethylene composition, 35 parts of an auxiliary resin, 12 parts of a filler, 1.1 parts of an antioxidant, 1.2 parts of an antistatic agent, 0.6 parts of a light stabilizer, 1.2 parts of a lubricant, 6 parts of a dispersant, 5.5 parts of a plasticizer, and 0.8 parts of a cross-linking agent.
[0070] The polyethylene composition is a composition of linear low-density polyethylene, low-density polyethylene and high-density polyethylene, and the mass ratio of the three is 50:30:15.
[0071] Example 3
[0072] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the polyethylene cling film, in parts by mass, are: 110 parts of a polyethylene composition, 25 parts of an auxiliary resin, 18 parts of a filler, 1.1 parts of an antioxidant, 1.2 parts of an antistatic agent, 0.6 parts of a light stabilizer, 1.2 parts of a lubricant, 8 parts of a dispersant, 5.5 parts of a plasticizer, and 0.8 parts of a cross-linking agent.
[0073] The polyethylene composition is a composition of linear low-density polyethylene, low-density polyethylene and high-density polyethylene, and the mass ratio of the three is 60:30:20.
[0074] Comparative Example 1
[0075] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the raw materials of the polyethylene cling film, in parts by mass, are: 120 parts of a polyethylene composition, 20 parts of an auxiliary resin, 5 parts of a filler, 1.1 parts of an antioxidant, 1.2 parts of an antistatic agent, 0.6 parts of a light stabilizer, 1.2 parts of a lubricant, 6.2 parts of a dispersant, 5.5 parts of a plasticizer, and 0.8 parts of a cross-linking agent.
[0076] Comparative Example 2
[0077] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the raw materials of the polyethylene cling film, in parts by mass, are: 95 parts of a polyethylene composition, 12 parts of an auxiliary resin, 25 parts of a filler, 1.1 parts of an antioxidant, 1.2 parts of an antistatic agent, 0.6 parts of a light stabilizer, 1.2 parts of a lubricant, 2.8 parts of a dispersant, 5.5 parts of a plasticizer, and 0.8 parts of a cross-linking agent.
[0078] Comparative Example 3
[0079] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified zinc oxide comprises the following steps: S1: 1.5 parts of zinc oxide and 1.5 parts of zirconium chloride hexahydrate are mixed and added to 80 parts of DMF solution, 0.6 parts of glutaric anhydride and 0.2 parts of 3-aminopropyltriethoxysilane are added, the temperature is raised to 70°C and kept warm for 2.5 hours, after completion, the product is centrifuged and filtered, and the pretreated mixed particles are obtained after washing and drying; S2: 1.6 parts of 1,4-phthalic acid and 0.2 parts of 1,4-aminophthalic acid are mixed and added to 80 parts of DMF solution, 0.6 parts of glutaric anhydride and 0.2 parts of 3-aminopropyltriethoxysilane are added, the temperature is raised to 70°C and kept warm for 2.5 hours, and the product is centrifuged and filtered, and the pretreated mixed particles are obtained after washing and drying; Formic acid is added to 100 parts of DMF and stirred thoroughly to form an acid mixed solution for use. 2.8 parts of pretreated mixed particles are dispersed in 40 parts of DMF solution and then added dropwise to the acid mixed solution. The dropping time is 1 hour and the dropping reaction temperature is 85°C. S3: After the dropping is completed, the reaction container is sealed, the temperature is raised to 130°C, and the reaction is kept warm for 18 hours. After completion, the product is naturally cooled to room temperature, and DMF and anhydrous ethanol are washed alternately for 3 times. Finally, the cleaned product is placed in a vacuum drying oven and dried overnight at 85°C.
[0080] The average particle size of the modified zinc oxide is 517 nm.
[0081] Comparative Example 4
[0082] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified zinc oxide comprises the following steps: S1: 0.6 parts of zinc oxide and 1.8 parts of zirconium chloride hexahydrate are mixed and added to 60 parts of DMF solution, 0.32 parts of glutaric anhydride and 0.08 parts of 3-aminopropyltriethoxysilane are added, the temperature is raised to 70°C and kept warm for 2.5 hours, after completion, the product is centrifuged and filtered, and the pretreated mixed particles are obtained after washing and drying; S2: 1.9 parts of 1,4-phthalic acid and 0.1 parts of 1,4-aminobenzene are mixed and added to 60 parts of DMF solution, 0.32 parts of glutaric anhydride and 0.08 parts of 3-aminopropyltriethoxysilane are added, the temperature is raised to 70°C and kept warm for 2.5 hours, and the product is centrifuged and filtered, and the pretreated mixed particles are obtained after washing and drying; Add diformic acid to 120 parts of DMF and stir thoroughly to form an acid mixed solution for use. Disperse 3.5 parts of pretreated mixed particles in 60 parts of DMF solution and then add dropwise to the acid mixed solution. The dropping time is 1 hour and the dropping reaction temperature is 85°C. S3: After the dropping is completed, seal the reaction container, heat it to 130°C, and keep the reaction for 18 hours. After completion, naturally cool the product to room temperature, wash it alternately with DMF and anhydrous ethanol for 3 times, and finally place the cleaned product in a vacuum drying oven and dry it overnight at 85°C.
[0083] The average particle size of the modified zinc oxide is 748 nm.
[0084] Comparative Example 5
[0085] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of zinc oxide is 45 nm; the average particle size of modified zinc oxide is 841 nm.
[0086] Comparative Example 6
[0087] The specific implementation of this comparative example is basically the same as that of Example 1, except that the dispersant is a composition of phenethylphenol polyoxyethylene ether and epoxy pre-stage polymer, and the mass ratio of the two is 6:0.8.
[0088] Comparative Example 7
[0089] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the epoxy front-stage polymer is a composition of an ethylene oxide-propylene oxide block copolymer with a weight average molecular weight of 1700Da (BASF, L42 model) and an ethylene oxide-propylene oxide block copolymer with a weight average molecular weight of 10000Da (BASF, L88 model), and the mass ratio of the two is 1:1.
[0090] Performance Evaluation
[0091] Mechanical test: The polyethylene cling film prepared in the embodiment and the comparative example was tested for mechanical tensile strength according to the standard GB / T 1040.3-2008. The test value was the average value of 10 tests and recorded in Table 1.
[0092] Salt spray corrosion resistance test: The polyethylene cling film prepared in the embodiment and the comparative example was tested for salt spray corrosion resistance, test reagent: 5wt% NaCl, test temperature: 35±2℃, test humidity: 95±2%, spraying amount: 2mL / (h·80cm 2 ), test time: 400h. After the test, check whether the samples are damaged, sulfonated, leaked or aged. If so, they are unqualified, otherwise they are qualified. 50 samples are tested in each group, and the test pass rate is recorded in Table 1.
[0093] Waterproof and moisture resistance test: refer to the standard GB / T 1037-1988 for testing, the test temperature is 25±2℃, the test humidity is 50±5%RH, and the test value is the average value of 10 tests and recorded in Table 1.
[0094] Heat aging test: Take 3cm×2.5cm×0.1cm samples of the polyethylene cling film prepared in the embodiments and comparative examples, test their tensile strength (MPa), then store the samples in a constant temperature and humidity environment of 75±2℃, 85±2% relative humidity for 14 days, take them out after 14 days, test their tensile strength (MPa) again, calculate and record the tensile strength retention rate after the test (%, tensile strength retention rate %) = tensile strength after test / tensile strength before test × 100%, and take the average value of 10 sample tests and record it in Table 1.
[0095] Table 1 Performance test results
[0096]
[0097] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of mechanical properties, waterproof properties, heat resistance, aging resistance and corrosion resistance. This is mainly due to the combined effect of the auxiliary resin, functional filler composition, specific dispersant and other matching technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. A polyethylene cling film, characterized in that: Polyethylene cling film, calculated by weight, comprises the following raw materials: 80-120 parts of polyethylene composition, 20-40 parts of auxiliary resin, 10-20 parts of filler, 1-2 parts of antioxidant, 1-1.5 parts of antistatic agent, 0.4-0.8 parts of light stabilizer, 0.5-1.5 parts of lubricant, 5-12 parts of dispersant, 3-6 parts of plasticizer, and 0.5-1 part of crosslinking agent; The polyethylene composition is a linear low-density polyethylene, a composition of low-density polyethylene and high-density polyethylene; The mass ratio of the linear low-density polyethylene, low-density polyethylene and high-density polyethylene is (40-60): (20-30): (10-20); The auxiliary resin is a composition of maleic anhydride grafted polyethylene and ethylene-vinyl acetate copolymer; The mass ratio of the maleic anhydride grafted polyethylene to the ethylene-vinyl acetate copolymer is (5-6): (1.5-2); The filler is a composition of talc, diatomaceous earth and modified zinc oxide; Preparation method of modified zinc oxide The following steps are involved: S1: Mix zinc oxide and zirconium chloride hexahydrate and add them to DMF solution, add glutaric anhydride and 3-aminopropyltriethoxysilane, heat to 70-75°C and keep warm for 2-3 hours, after completion, centrifuge and filter the product, wash and dry to obtain pretreated mixed particles; S2: Add 1,4-phthalic acid and 1,4-aminophthalic acid to DMF and stir to form an acid mixed solution for use, disperse the pretreated mixed particles in the DMF solution and then add them dropwise to the acid mixed solution, the dropwise addition time is 1-1.5 hours, and the dropwise addition reaction temperature is 80-90°C; S3: After the dropwise addition is completed, seal the reaction container, heat to 120-140°C, keep warm for 16-18 hours, after completion, naturally cool the product to room temperature, wash alternately with DMF and anhydrous ethanol 2-3 times, and finally place the cleaned product in a vacuum drying oven, dry it overnight at 80-90°C, and the product is completed; The mass ratio of the zinc oxide, zirconium chloride hexahydrate, glutaric anhydride and 3-aminopropyltriethoxysilane is (0.5-0.8): (1.5-2): (0.3-0.4): (0.05-0.1); In the pretreated mixed particles, the mass ratio of 1,4-phthalic acid to 1,4-aminophthalic acid is (2-2.5): (1.2-1.5): (0.3-0.5).
2. The polyethylene cling film according to claim 1, characterized in that: The mass ratio of the polyethylene composition, the auxiliary resin and the filler is (95-110): (25-35): (12-18).
3. The polyethylene cling film according to claim 2, characterized in that: The mass ratio of the talc powder, diatomaceous earth and modified zinc oxide is (4-5): (1-2): (7-9).
4. The polyethylene cling film according to claim 3, characterized in that: The average particle size of the talc powder is 1 to 1.5 μm.
5. The polyethylene cling film according to claim 4, characterized in that: The average particle size of the zinc oxide is 15-20 nm; the average particle size of the modified zinc oxide is 620-720 nm.
6. The polyethylene cling film according to claim 5, characterized in that: The lubricant is a composition of zinc stearate and glyceryl stearate; the mass ratio of zinc stearate to glyceryl stearate is (5-7): (2-2.5).
7. The polyethylene cling film according to claim 6, characterized in that: The dispersant is a composition of phenethylphenol polyoxyethylene ether and epoxy front-stage polymer; the mass ratio of the phenethylphenol polyoxyethylene ether and the epoxy front-stage polymer is (3-3.5): (1.5-2); the HLB value of the phenethylphenol polyoxyethylene ether is 10-14.
8. The polyethylene cling film according to claim 7, characterized in that: The weight average molecular weight of the epoxy front-stage polymer is 1500-5000Da.
9. A method for preparing a polyethylene cling film according to any one of claims 1 to 8, characterized in that: The specific steps include: S1: The polyethylene composition, auxiliary resin, filler and dispersant are mixed and added into a high-speed mixer, and mixed evenly at a rotation speed of 600-800 rpm for 30-35 min. After completion, the remaining raw materials are added, the rotation speed is increased to 1200-1500 rpm, and mixed for 10-15 min. S2: The mixed raw materials are added into a twin-screw extruder, and the temperature of the extruder is set to 180-220° C. and the screw speed is set to 200-300 rpm for melt extrusion. The extruded melt is extruded into a film through a die head. S3: The extruded film melt is quickly cooled and shaped by a water-cooled roller, the temperature of the water-cooled roller is controlled at 20-30° C., and the cooling speed is 2-4 m / min. S4: The film after cooling and shaping is towed by a towing device at a towing speed of 5-7 m / min, and then rolled up. After completion, it is obtained.
10. Use of the polyethylene cling film according to any one of claims 1 to 9 in the field of rubber tires.